2010
DOI: 10.1016/j.survophthal.2009.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Nonarteritic Anterior Ischemic Optic Neuropathy

Abstract: Nonarteritic anterior ischemic optic neuropathy (NAION) is the most common clinical presentation of acute ischemic damage to the optic nerve. Most treatments proposed for NAION are empirical and include a wide range of agents presumed to act on thrombosis, on the blood vessels, or on the disc edema itself. Others are presumed to have a neuroprotective effect. Although there have been multiple therapies attempted, most have not been adequately studied, and animal models of NAION have only recently emerged. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 87 publications
2
97
0
11
Order By: Relevance
“…Rarely, human AION is treated with anti-VEGF or steroids. 17,18 Certainly, ischemia could lead to the upregulation of VEGF and perhaps contribute to the formation of subretinal fluid. However, anti-VEGF therapy has been associated with exacerbation of retinal ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, human AION is treated with anti-VEGF or steroids. 17,18 Certainly, ischemia could lead to the upregulation of VEGF and perhaps contribute to the formation of subretinal fluid. However, anti-VEGF therapy has been associated with exacerbation of retinal ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…A large non-randomized study revealed that patients with optic disc edema from acute NAION who received oral prednisone initiated at a dose of 80 milligrams daily for 2 weeks with a taper had improved visual outcomes compared with untreated controls [62]. Because of the limitations of the study design and potential biases in the two populations studied, these results must be interpreted with caution [7]. Indeed, the controversies surrounding the use of corticosteroids in NAION stem mainly from a lack of Class I evidence supporting the efficacy of the intervention, as well as the potential risks of the intervention [63].…”
Section: Treatmentmentioning
confidence: 98%
“…There is no sex predilection for NAION. With respect to race, whites appear to be more likely to develop the condition than minority populations [5,6], possibly due to risk factors associated with optic disc morphology [7,8].…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations